Identification of natural compounds as SARS-CoV-2 inhibitors via molecular docking and molecular dynamic simulation - Han, Tiantian; Luo, Ziqing; Ji, Lichun; Wu, Peng; Li, Geng; Liu, Xiaohong; Lai, Yanni (Frontiers in Microbiology, 2023)
Background: Base mutations increase the contagiousness and transmissibility of the Delta and Lambda strains and lead to the severity of the COVID-19 pandemic. Molecular docking and molecular dynamics (MD) simulations are frequently used for drug discovery and relocation. Small molecular compounds from Chinese herbs have an inhibitory effect on the virus. Therefore, this study used computational simulations to investigate the effects of small molecular compounds on the spike (S) protein and the binding between them and angiotensin-converting enzyme 2 (ACE2) receptors. Methods: In this study, molecular docking, MD simulation, and protein-protein analysis were used to explore the medicinal target inhibition of Chinese herbal medicinal plant chemicals on SARS-CoV-2. 12978 phytochemicals were screened against S proteins of SARS-CoV-2 Lambda and Delta mutants. Results: Molecular docking showed that 65.61% and 65.28% of the compounds had the relatively stable binding ability to the S protein of Lambda and Delta mutants (docking score ≤ -6). The top five compounds with binding energy with Lambda and Delta mutants were clematichinenoside AR2 (-9.7), atratoglaucoside,b (-9.5), physalin b (-9.5), atratoglaucoside, a (-9.4), Ochnaflavone (-9.3) and neo-przewaquinone a (-10), Wikstrosin (-9.7), xilingsaponin A (-9.6), ardisianoside G (-9.6),23-epi-26-deoxyactein (-9.6), respectively. Four compounds (Casuarictin, Heterophylliin D, Protohypericin, and Glansrin B) could interact with S protein mutation sites of Lambda and Delta mutants, respectively, and MD simulation results showed that four plant chemicals and spike protein have good energy stable complex formation ability. In addition, protein-protein docking was carried out to evaluate the changes in ACE2 binding ability caused by the formation of four plant chemicals and S protein complexes. The analysis showed that the binding of four plant chemicals to the S protein could reduce the stability of the binding to ACE2, thereby reducing the replication ability of the virus. Conclusions: To sum up, the study concluded that four phytochemicals (Casuarictin, Heterophylliin D, Protohypericin, and Glansrin B) had significant effects on the binding sites of the SARS-Cov-2 S protein. This study needs further in vitro and in vivo experimental validation of these major phytochemicals to assess their potential anti-SARS-CoV-2.